Examining the relationship between neuroticism and post-concussion syndrome in mild traumatic brain injury. (3rd July 2019) - Merz, Zachary C.; Zane, Katherine; Emmert, Natalie A.; Lace, John; Grant, Alexandra
ABSTRACT: Objective : We sought to examine the relationship between personality traits and post-concussion symptom reporting in individuals with and without a self-reported history of concussion. Methods : Data were collected via a cross-sectional electronic survey from 619 individuals via Amazon Mechanical Turk (mTurk). Participants completed a background demographic questionnaire, as well as both the Post-Concussion Symptom Scale (PCSS) and IPIP-NEO-120 personality inventory. Results : Significant relationships were seen between concussion symptom reporting and personality traits of neuroticism, extraversion, agreeableness, and conscientiousness, but not openness, among both groups. The positive concussion group reported more severe symptoms across nearly all PCSS items, despite being, on average, multiple years removed from their injury. Furthermore, broad personality traits did not differ between concussion groups. Discussion : The positive concussion group reported persisting symptoms many years post-injury, suggesting a small subset of individuals may not become fully asymptomatic following a concussion. While differences among personality traits, including neuroticism, were not seen, psychiatric distress, namely symptoms of depression, accounted for a significant degree of variance in symptom reporting and is likely a strong influencer in recovery trajectory. As such, an increased emphasis on psychotherapeutic treatment following a concussion, especially in cases with prolonged recovery, may be warranted.